PENGARUH PENAMBAHAN KAWAT BENDRAT DAN SERBUK KACA TERHADAP KUAT TEKAN PADA PAVING - Emerson Fitti Valdi; Sri Agustin; Lisa Trisnawati (Nusantara Hasana Berdikari, 2022)
Some requirements for paving must have physical properties according to SNI 03-0691-1996 regarding paving, namely compressive strength, wear resistance, and absorption. Efforts to improve these properties can be done by adding fiber to the mixture. The use of glass waste and bendrat wire in partial replacement of fine aggregate is expected to be an alternative to various problems in the construction and environmental world. According to (Soroushian & Bayasi, 1987) the basic idea of ​​adding fiber is to provide reinforcement in concrete with steel fibers that are evenly distributed into the concrete mix which can prevent premature cracks in the concrete, either due to heat of hydration or due to loading, so that expected to be able to increase ductility, abrasion resistance, compressive strength, tensile strength, flexural strength, resistance to shrinkage, fracture and peeling. The compressive strength of standard paving already has good strength, with the addition of glass waste and bendrat wire as fine aggregate, it is expected to be able and further increase the compressive strength of the paving. From the results of research and testing, it can be seen that the effect of adding variations in the mixture of 0%, 5%, 10%, and 15% bendrat wire and glass powder to the compressive strength of paving can increase the compressive strength of concrete by 36.26 Mpa, 46.12, respectively. Mpa, 50.15 Mpa and 55.66 Mpa. The addition of bendrat wire and paving glass powder can increase the value of the compressive strength of paving and is recommended as an additional fiber for paving, with the addition of bendrat wire and glass powder 15% with a percentage increase of 10.2%.